Poor quality care in healthcare settings: an overlooked epidemic - Augustine Kumah (Frontiers in Public Health)
Adverse events in healthcare settings, including medical errors, healthcare-associated infections (HAIs), and surgical complications, have been a persistent challenge globally, contributing significantly to patient morbidity and mortality. Over the past decade, these events have remained prevalent despite increasing efforts to improve patient safety. This narrative literature review explores the burden of poor-quality care. It examines the trends in adverse events and associated mortalities from 2015 to 2024, highlighting the impact of these events on global health outcomes and identifying potential strategies for reducing their occurrence. Data were collected from various sources such as PubMed, Google Scholar, Scopus, and Ebscohost. The analysis revealed that ~10%−12% of hospitalized patients in high-income countries experienced adverse events annually from 2015 to 2024. Globally, the WHO estimated that 134 million adverse events occurred each year, with ~2.6 million deaths attributed to these events. Adverse events in healthcare settings remain a significant public health challenge, contributing to millions of preventable deaths annually. The persistence of these events highlights systemic issues within healthcare delivery, including inadequate safety protocols, underreporting, and workforce challenges.